2020
DOI: 10.1021/acscatal.0c03346
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oxygenates Formation in the Fischer–Tropsch Synthesis over Co- and/or Ni-Containing Fe Alloys: Characterization and 2D Gas Chromatographic Product Analysis

Abstract: Transition metal alloys are receiving considerable attention in heterogeneous catalysis as they hold promise to combine advantageous properties of the constituting metals and, therefore, provide attractive avenues for targeted catalyst design. The present study concerns the effect of Co and Ni substituents in the ferrite (Fe 3 O 4 ) structure used as a catalyst precursor for medium-temperature Fischer−Tropsch (MTFT) synthesis, in anticipation of enhanced oxygenate selectivities. The ferrites were synthesized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 121 publications
(195 reference statements)
0
7
0
Order By: Relevance
“…One of the advantages of targeting the spinel structure is the possibility of achieving high loadings of the dopant in the final catalyst [39]. Moreover, the uniform distribution of Mg in the catalysts may result in an optimized effect of Mg during CO-PrOx due to its close proximity to Fe or Co [33,39].…”
Section: Fresh Catalyst Characterisationmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the advantages of targeting the spinel structure is the possibility of achieving high loadings of the dopant in the final catalyst [39]. Moreover, the uniform distribution of Mg in the catalysts may result in an optimized effect of Mg during CO-PrOx due to its close proximity to Fe or Co [33,39].…”
Section: Fresh Catalyst Characterisationmentioning
confidence: 99%
“…One of the advantages of targeting the spinel structure is the possibility of achieving high loadings of the dopant in the final catalyst [39]. Moreover, the uniform distribution of Mg in the catalysts may result in an optimized effect of Mg during CO-PrOx due to its close proximity to Fe or Co [33,39]. The CO-PrOx reaction is carried out under a reducing environment due to the high concentration of H2 (typically between 40 and 75 vol.%) [5,6,40,41].…”
Section: Catalystmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrocarbon selectivity can be optimized by adjusting the geometric and electronic properties of the FTS catalyst. In recent years, various types of strategies have been adopted to cope up with the defined challenges, such as core–shell structure, promoters, and supports . Bimetallic catalysts with an alloy or spinel structure were also studied by some other researchers. Most research conducted on Fe and Co and a proper percentage of bimetallic catalysts showed enhanced activity compared to the monometallic Fe and Co catalysts . However, some other research shows reverse results .…”
Section: Introductionmentioning
confidence: 99%